Parental occupational exposure to pesticides, animals and organic dust and risk of childhood leukemia and central nervous system tumors: Findings from the International Childhood Cancer Cohort Consortium (I4C) - Patel, DM; Jones, RR; Booth, BJ; Olsson, AC; Kromhout, H; Straif, K; Vermeulen, R; Tikellis, G; Paltiel, O; Golding, J; Northstone, K; Stoltenberg, C; et al. (Wiley, 2019)
Parental occupational exposures to pesticides, animals and organic dust have been associated with an increased risk of childhood cancer based mostly on case–control studies. We prospectively evaluated parental occupational exposures and risk of childhood leukemia and central nervous system (CNS) tumors in the International Childhood Cancer Cohort Consortium. We pooled data on 329,658 participants from birth cohorts in five countries (Australia, Denmark, Israel, Norway and United Kingdom). Parental occupational exposures during pregnancy were estimated by linking International Standard Classification of Occupations‐1988 job codes to the ALOHA+ job exposure matrix. Risk of childhood (<15 years) acute lymphoblastic leukemia (ALL; n = 129), acute myeloid leukemia (AML; n = 31) and CNS tumors (n = 158) was estimated using Cox proportional hazards models to generate hazard ratios (HR) and 95% confidence intervals (CI). Paternal exposures to pesticides and animals were associated with increased risk of childhood AML (herbicides HR = 3.22, 95% CI = 0.97–10.68; insecticides HR = 2.86, 95% CI = 0.99–8.23; animals HR = 3.89, 95% CI = 1.18–12.90), but not ALL or CNS tumors. Paternal exposure to organic dust was positively associated with AML (HR = 2.38 95% CI = 1.12–5.07), inversely associated with ALL (HR = 0.55, 95% CI = 0.31–0.99) and not associated with CNS tumors. Low exposure prevalence precluded evaluation of maternal pesticide and animal exposures; we observed no significant associations with organic dust exposure. This first prospective analysis of pooled birth cohorts and parental occupational exposures provides evidence for paternal agricultural exposures as childhood AML risk factors. The different risks for childhood ALL associated with maternal and paternal organic dust exposures should be investigated further.